Consensual Budgetary and Fiscal Policy of BRICS - М. V. Zharikov (Учёт. Анализ. Аудит)
The research is relevant as it defnes the optimal level of taxation for the BRCS members in the frames of consensual tax, budgetary and fscal policy in order to achieve the sustainable rate of economic growth, balanced development, moderate rates of inﬂation, high volume of production, balance of current account and low unemployment. The development of the BRICS countries as a new model of integration and inclusive development in the globalizing economy requires consensual macroeconomic policy. The author hypothesizes that consensual macroeconomic (tax and budgetary policy) may contribute to the harmonization of national economies of the BRICS members by parameters of an integration model proposed in the article. As a result of economic and mathematical modeling there were drafted the curves of the BRICS members’ budget revenue and expenditure. The author identifes the optimal weighted average tax rates to establish the balance. The graphic method is used to demonstrate the inﬂuence of tax, budgetary and fscal policy of the BRICS members on national economies and combined effect of its implementation. The practical importance of the research lies in identifying the optimal level of taxation which makes it possible to balance the BRICS members’ budgets. The calculation of the effectiveness of consensual tax, budgetary and fscal policy of the BRICS members is made on the basis of comparative analysis of the variants of fnancing the budget defcit by own means and the sources of hypothetical common debt market. The article proves that functioning of common market of debt fnance is optimal for the BRICS members on condition of using comparative advantage of China in providing credit resources to the members of the group. The theoretical signifcance of the results is the development of the methodology of harmonization of tax, budgetary and fscal policy of the BRICS members using gradual approach as opposite to “shock therapy” scenario.